Proceedings of the Ocean Drilling Program 1995
DOI: 10.2973/odp.proc.sr.141.002.1995
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy of Sediments from the Chile Triple Junction

Abstract: Quaternary and Pliocene terrigenous sediments recovered during Ocean Drilling Program Leg 141 on the Chile Trench continental slope are represented by hemipelagic mud and distal and proximal turbidites with minor gravity-flow deposits. The coarse fraction is composed mainly of quartz and feldspars, with hornblende, epidote, and clinopyroxene dominating the heavy fraction. Volcanic glass, mica, orthopyroxene, tremolite-actinolite, olivine and "sialic" accessories (garnet, zircon, apatite, tourmaline, and sphene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…This difference can mostly be attributed to the variety of source rocks. The clay association is comparable to that of sediments from the relatively close Chile triple junction (Kurnusov et al, 1995), but is different from sediments in the Chile margin at 43ºS, which are characterized by greater smectite contents, reflecting a warmer climate and stronger chemical weathering processes (Lamy et al, 1998a,b).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…This difference can mostly be attributed to the variety of source rocks. The clay association is comparable to that of sediments from the relatively close Chile triple junction (Kurnusov et al, 1995), but is different from sediments in the Chile margin at 43ºS, which are characterized by greater smectite contents, reflecting a warmer climate and stronger chemical weathering processes (Lamy et al, 1998a,b).…”
Section: Discussionmentioning
confidence: 76%
“…The bulk sediment composition of hemipelagic sediments from the the southern Chilean margin differs from that of sediments deposited in more northern sectors of the South American continental margin in terms of the large biogenic carbonate content, as in the latter areas they are much smaller (Kurnusov et al, 1995;Hebbeln et al, 2000). As we did not acid-treat the silicate samples to remove the The sediments of the cores studied are characterized by slightly smaller contents of quartz and plagioclase, and increased alkali feldspar and mica contents, with respect to sediments collected at the northernmost latitude such as the Chile triple junction (Kurnusov et al, 1995) and Chilean continental margin at 43ºS (Lamy et al, 1998a). In general, the quartz content of the sediments along the Chilean margin decreases from northern to southern latitudes.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…For adjacent areas examinations of surface sediments exist for the continental margin off Peru and northern Chile (Krissek et al 1980;Rosato and Kulm 1981;Scheidegger and Krissek 1982) and shelf areas of the Chilean archipelago (Siegel et al 1981). Additionally, terrigenous sediments, recovered during ODP leg 112 on the Peruvian continental margin (Clayton and Kemp 1990) and ODP leg 141 near the Chile triple junction (Kurnosov et al 1995), were analyzed concerning mainly the clay mineralogy.…”
Section: F Lamy · D Hebbeln · G Wefermentioning
confidence: 99%
“…42°S-55°S (Siegel et al 1981) and at ca. 46°S (Kurnosov et al 1995) revealed illite-and chlorite-dominated assemblages. Therefore, the differing clay mineralogy of these offshore samples might indicate lateral input from southern areas or pelagic areas to the west as the Antarctic Circumpolar Current approaches South America in this area (see Oceanographic setting).…”
Section: Clay Mineralogymentioning
confidence: 99%